Aadhunik Hindi Dalit Vimarsh Tatha Moonshi Premchand Ki Kaljayi Dalit Kahani Evam Unke Patron Ka Adhyayan: An in-depth study of contemporary Hindi Dalit literature and the works of Moonshi Premchand (Journal of Advances and Scholarly Researches in Allied Education, 2012)
no